KEPUASAN PASIEN JAMKESMAS TERHADAP KUALITAS PELAYANAN KESEHATAN DI POLI UMUM PUSKESMAS PETALING KABUPATEN BANGKA TAHUN 2009 - Nur Alam Fajar; Erma Kartikasari; Asmaripa Ainy (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Community Health Insurance is the government's social assistance programs for the poor. Research from the Indonesian Corruption Watch (ICW) found out that the quality of health services for the poor through the program of community health insurance is still low. This problem can be seen from the report of implementation program JPKM ASKESKIN in 2007 and report on the implementation of public health insurance program in 2008 at Petaling Health Center that decreased the number of patient visits by 60,52%. Therefore, this study aims to determine patient satisfaction of community health insurance to quality health services at the General Out Patient Clinic Petaling Public Health Center of Bangka. This research is a quantitative study using importance-performance analysis. This sample amount of 73 patients of community health insurance taken by purposive sampling technique. Tools of data collection primary data derived from the results of questionnaires and secondary dataderived from health profiles Petaling Public Health Center. The results of this study indicated that the average value of fitness levels for all dimensions are 82.49% which the level of concordance 78.47% reliability dimension, responsiveness 80.70%, assurance 85.01%, empathy 82.68% and tangible 85, 63%. Based on the importance-performance analysis of 25 factors which are investigated there are 8 (eight) factors that are in quadrant I, 7 (seven) factors in quadrant II, 3 (three) factors in quadrant III and 7 (seven) factors in quadrant IV. Advice given to the Petaling Health Center of Bangka is to improve health worker performance in terms of reliability and responsiveness in a way to supervise the implementation of service provided and give awards to outstanding officers. In addition, health workers also need to maintain the performance of the services provided in terms of empathy, assurance and tangibles with means to evaluate the services routinely provided.